Bilingual Teachers’ Competencies in Language Teaching: A Systematic Literature Review - Reni Dwita Putri; Ummi Rasyidah (English Language Education, Universitas Internasional Batam, 2026)
The increasing diversity of multilingual classrooms has heightened the demand for competent bilingual teachers in language education. This study aimed to systematically review existing literature on bilingual teachers’ competencies in language teaching. A systematic literature review (SLR) following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted for the period 2021–2025 using databases including Scopus, Web of Science, ERIC, and Google Scholar. A total of 117 records were identified, and following a rigorous screening process, 35 peer-reviewed studies were included in the final synthesis. The findings identified four core competency dimensions: linguistic, communicative and intercultural, cognitive, and bilingual pedagogical competence. Dominant bilingual teaching methods included translanguaging, Content and Language Integrated Learning, structured code-switching, and bilingual scaffolding. Professional development emerged as a critical yet unevenly distributed pillar across educational systems globally a gap documented consistently across studies from diverse national contexts encompassing pre-service preparation, reflective practice, and collaborative learning communities. This review concluded that bilingual teacher competence is multidimensional and must be developed holistically. Practically, teacher education institutions are urged to redesign pre-service curricula to incorporate translanguaging pedagogy and intercultural competence, while policymakers should establish evidence-based competency frameworks supported by adequate resources and mentorship structures.